ANALYSIS OF THE 'URF CONCERNING THE PROHIBITION OF NGALOR NGULON MATRIMONY IN TUMPAKKEPUH VILLAGE, BAKUNG, BLITAR - Rivaniansyah Siacahyo Winarno; Saipul Nasution; Jamhuri; Iman Nur Hidayat; Meitria Cahyani (Sahaja: Journal Sharia and Humanities, 2025)
This study examines the practice of preventing marriage known as "Ngalor Ngulon" in Tumpakkepuh Village, which is primarily Muslim. This custom forbids marriage if the prospective groom's residence is situated in the north-west direction relative to the prospective bride's residence, as it is considered to result in calamities such as discord, mortality, or financial hardships. This research employs a qualitative methodology utilizing a sociological-legal framework. Data were collected via interviews with village heads, traditional authorities, religious leaders, and community members, in addition to direct observation. Literary analyses pertaining to Islamic jurisprudence concerning 'urf and matrimony further substantiate this research. The study's findings indicate that the practice of "Ngalor Ngulon" is categorized as 'urf fasid due to its lack of foundation in Islamic law. Islam does not forbid marriage depending on the orientation of the residence; instead, it underscores the fundamental principles and prerequisites of marriage. This tradition is preserved as a cultural heritage. This study aims to enhance the community's comprehension of the Islamic notion of marriage and to illuminate scholars' perspectives on the interplay between local customs and sharia law.